Sampling strategies for phlebotomine sand flies (Diptera: Psychodidae) in Europe. Issue 6 (14th August 2015) - Alten, B.; Ozbel, Y.; Ergunay, K.; Kasap, O.E.; Cull, B.; Antoniou, M.; Velo, E.; Prudhomme, J.; Molina, R.; Bañuls, A.-L.; Schaffner, F.; Hendrickx, G.; et al.
Abstract: The distribution of phlebotomine sand flies is widely reported to be changing in Europe. This can be attributed to either the discovery of sand flies in areas where they were previously overlooked (generally following an outbreak of leishmaniasis or other sand fly-related disease) or to true expansion of their range as a result of climatic or environmental changes. Routine surveillance for phlebotomines in Europe is localized, and often one of the challenges for entomologists working in non-leishmaniasis endemic countries is the lack of knowledge on how to conduct, plan and execute sampling for phlebotomines, or how to adapt on-going sampling strategies for other haematophagous diptera. This review brings together published and unpublished expert knowledge on sampling strategies for European phlebotomines of public health concern in order to provide practical advice on: how to conduct surveys; the collection and interpretation of field data; suitable techniques for the preservation of specimens obtained by different sampling methods; molecular techniques used for species identification; and the pathogens associated with sand flies and their detection methods.